Effect of Snow Salinity on CryoSat‐2 Arctic First‐Year Sea Ice Freeboard Measurements. Issue 20 (17th October 2017) - Nandan, Vishnu; Geldsetzer, Torsten; Yackel, John; Mahmud, Mallik; Scharien, Randall; Howell, Stephen; King, Joshua; Ricker, Robert; Else, Brent
Abstract: The European Space Agency's CryoSat‐2 satellite mission provides radar altimeter data that are used to derive estimates of sea ice thickness and volume. These data are crucial to understanding recent variability and changes in Arctic sea ice. Sea ice thickness retrievals at the CryoSat‐2 frequency require accurate measurements of sea ice freeboard, assumed to be attainable when the main radar scattering horizon is at the snow/sea ice interface. Using an extensive snow thermophysical property dataset from late winter conditions in the Canadian Arctic, we examine the role of saline snow on first‐year sea ice (FYI), with respect to its effect on the location of the main radar scattering horizon, its ability to decrease radar penetration depth, and its impact on FYI thickness estimates. Based on the dielectric properties of saline snow commonly found on FYI, we quantify the vertical shift in the main scattering horizon. This is found to be approximately 0.07 m. We propose a thickness‐dependent snow salinity correction factor for FYI freeboard estimates. This significantly reduces CryoSat‐2 FYI retrieval error. Relative error reductions of 11% are found for an ice thickness of 0.95 m and 25% for 0.7 m. Our method also helps to close the uncertainty gap between SMOS and CryoSat‐2 thin ice thickness retrievals. Our results indicate that snow salinity should be considered for FYI freeboard estimates. Key Points: First empirically derived assessment of the influence of snow salinity on Arctic first‐year sea ice (FYI) thickness from CryoSat‐2 Snow salinity affects FYI thickness estimates from CryoSat‐2 by shifting the main radar scattering horizon upward into the snow cover A semi‐empirically derived snow salinity correction factor is proposed for completing current methods to retrieve CryoSat‐2 FYI freeboard